2006
DOI: 10.1152/ajprenal.00329.2005
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive hyperfiltration in the aging kidney after contralateral nephrectomy

Abstract: We examined the magnitude of adaptive hyperfiltration in the remaining kidney of 16 aging (Ͼ57 yr) and 16 youthful (Ͻ55 yr) individuals who had undergone a contralateral nephrectomy. Healthy volunteers who were youthful (n ϭ 143) or aging (n ϭ 37) provided control values for the binephric condition. One-kidney glomerular filtration rate (GFR; ϩ42%), renal plasma flow (ϩ38%), plasma oncotic pressure (ϩ2.8 mmHg), and mean arterial pressure (ϩ7.0 mmHg) were all higher in youthful uninephric vs. binephric subjects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
35
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 50 publications
(35 citation statements)
references
References 32 publications
0
35
0
Order By: Relevance
“…In healthy subjects, unilateral nephrectomy is followed by a compensatory increase of the contralateral kidney function. This compensation is approximately a 20-40 % increase in GFR from baseline [16][17][18][19][20]. Velosa et al among others showed that as early as 1-week post-nephrectomy, renal function has recovered to levels slightly lower than those achieved at 6 months post-nephrectomy.…”
Section: Donor Kidney Function and Its Implications To The Donormentioning
confidence: 99%
See 2 more Smart Citations
“…In healthy subjects, unilateral nephrectomy is followed by a compensatory increase of the contralateral kidney function. This compensation is approximately a 20-40 % increase in GFR from baseline [16][17][18][19][20]. Velosa et al among others showed that as early as 1-week post-nephrectomy, renal function has recovered to levels slightly lower than those achieved at 6 months post-nephrectomy.…”
Section: Donor Kidney Function and Its Implications To The Donormentioning
confidence: 99%
“…The mechanisms of this compensatory hyperfiltration are complex and determined by several factors [18]. Age and body size may be important determinants of the change in GFR following donation.…”
Section: Donor Kidney Function and Its Implications To The Donormentioning
confidence: 99%
See 1 more Smart Citation
“…Immediately following nephrectomy, an approximately 40% increase in renal plasma flow (RPF) and glomerular filtration rate (GFR) in the remaining kidney ensues (6,7). This is associated with glomerular hypertrophy, which may contribute to the adaptive hyperfiltration by enhancing the filtration surface area and hence the whole-kidney ultrafiltration coefficient (K f ) (7).…”
Section: Introductionmentioning
confidence: 99%
“…This is associated with glomerular hypertrophy, which may contribute to the adaptive hyperfiltration by enhancing the filtration surface area and hence the whole-kidney ultrafiltration coefficient (K f ) (7). Another hypothetical contribution to hyperfiltration is an increase in glomerular capillary -and hence ultrafiltration -pressure.…”
Section: Introductionmentioning
confidence: 99%